DA POLÍTICA DE INSTANTE À POLÍTICA PARA O INSTANTE : uma crítica de políticas públicas de lazer no Brasil - Silveira, Shaiane Vargas da (2015)
This dissertation presents a critical analysis of the contents, the agenda, the subject and the trajectory of these institutional policies within the Federal Government in Brazil in order to understand how it is possible to overcome the contradictions of leisure and break the logic of capital through interventions promoted by the State. The construction of such critical analysis envisaged the theoretical framework presenting the leisure contradictions stimulated by capitalist social relations. The collection of international protocols related to leisure revealed the international public agenda with its historical legacy and ideological repercussions that have influenced, and still influence, the legal-institutional framework of public action, subordinating it to the hegemonic maintenance of capital. The following chapter presents the historic rescue of the subjects and of public policies for national leisure characterized, in different times, by moralist and hygienist interventions; by the valuation of aesthetic patterns and social status; by working-class control; by populism and mass alienation; and, lastly, by functionalist and fragmented interventions that promote leisure as a consumer product. A proper systematic analysis was used to identify what the study calls "Instant Policy". Ratifying leisure as an instantaneous and discontinued experience, whose main benefit is given by the immediate consumption of goods produced by the market of entertainment or sports and the cultural industry, the "Instant Policy is confronted with the proposal of "Policy for the Moment", which takes a structured set of goals covering the instant as an experiential moment of leisure, being part of the lasting stream of composition of a varied repertoire of experiences, which is presented as an alternative to overcome the logic of capital that has been influencing public policies for leisure in Brazil.